2022
DOI: 10.1039/d2qo00490a
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative cyclization of o-chlorobenzoic acids with C,C-palladacycles formed by an aminopalladation/dealkylation strategy to access dibenzo[a,c]carbazoles

Abstract: Herein a novel palladium-catalyzed tandem decarboxylative biscyclization of o-alkynylanilines with o-chlorobenzoic acids has been reported, which provides an efficient approach for the assembly of dibenzo[a,c]carbazoles. This protocol employs an intramolecular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…Subsequently, our group and others designed various halogenated carboxylic acids as C1, C2 or C3 insertion units to construct different size-ring fused cyclic compounds via this strategy. [53][54][55][56][57][58][59][60][61][62] In these reactions, it was observed that the inser- tion of carboxylic acids usually showed good regioselectivity. Thus, the methods used o-halobenzoic acids, arynes and aryl halides as aromatic ring precursors, which could be complementary.…”
Section: Palladium-catalysed Intermolecular C-h Annulation Of Aryl Ha...mentioning
confidence: 99%
“…Subsequently, our group and others designed various halogenated carboxylic acids as C1, C2 or C3 insertion units to construct different size-ring fused cyclic compounds via this strategy. [53][54][55][56][57][58][59][60][61][62] In these reactions, it was observed that the inser- tion of carboxylic acids usually showed good regioselectivity. Thus, the methods used o-halobenzoic acids, arynes and aryl halides as aromatic ring precursors, which could be complementary.…”
Section: Palladium-catalysed Intermolecular C-h Annulation Of Aryl Ha...mentioning
confidence: 99%
“…The key feature of this reaction protocol reflects palladium and norbornene/norbornadiene-cocatalyzed π-extended dehalogenation/decarboxylation double coupling reactions. Following this elegant reaction protocol, a large range of privileged polycyclic aromatic scaffolds represented with phenanthrenes, benzofulvenes, benzopyrans, benzocarbazoles, triphenylenes, and many other fused and spiro polycyclic heteroarenes were readily constructed from simple aryl iodides. However, an inevitable problem involved in these palladium-catalyzed annulation protocols is reaction regioselectivity; 2-halobenzoic acids possess two possible reaction pathways: sequential dehalogenation/decarboxylation double coupling and sequential decarboxylation/dehalogenation double coupling, leading to a mixture of regioisomers .…”
mentioning
confidence: 99%